Attitudes on wildfire evacuation: Exploring the intended evacuation behavior of residents living in two Southern California communities - Roberson, B.; Peterson, D.; Parsons, Richard (Weston Medical Publishing, LLC, 2012)
Residents living within the Wildland-Urban Interface who fail to immediately evacuate during wildfire emergencies may not only increase the risk of injury or death to themselves but also to firefighters and rescuers tasked to protect them. In the coastal mountains of Santa Barbara County, CA, data on intended resident wildfire evacuation behavior does not exist. This research study used self-administered mail surveys to collect data on attitudes toward wildfire evacuation from more than 200 residents living within the High Fire Hazard Area of the Carpinteria Summerland Fire District (CA). Data derived from completed surveys indicate that although most residents intend to evacuate when given either voluntary or mandatory orders, 10 percent do not. A multivariate analysis performed on these residents indicates that men are less likely to evacuate than women, and long-term residents are less likely to evacuate than short-term residents. Further analysis of these residents indicates a wide variety of reasons for evacuation noncompliance, which are discussed in this study. Based on the results of these analyses, this research study provides recommendations to local public safety officials so they may better prepare for future wildfire evacuation events.